2017
DOI: 10.1159/000485418
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 70 Negatively Regulates TGF-β-Stimulated VEGF Synthesis via p38 MAP Kinase in Osteoblasts

Abstract: Background/Aims: We previously demonstrated that transforming growth factor-β (TGF-β) stimulates the synthesis of vascular endothelial growth factor (VEGF) through the activation of p38 mitogen-activated protein (MAP) kinase in osteoblast-like MC3T3-E1 cells. Heat shock protein70 (HSP70) is a ubiquitously expressed molecular chaperone. In the present study, we investigated the involvement of HSP70 in the TGF-β-stimulated VEGF synthesis and the underlying mechanism in these cells. Methods: Culture MC3T3-E1 cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 50 publications
1
11
0
Order By: Relevance
“…Here, we have shown for the first time that DMF attenuates expression of VEGF mRNA and its release from RPE cells exposed to HG. Since the p38 MAPK pathway promotes and regulates the expression of pro-angiogenesis factors, including VEGF (Gomes and Rockwell, 2008;Sakai et al, 2017) we sought to determine whether VEGF decrease could rely on a DMF-induced p38 MAPK down-regulation. Therefore, we performed Western blot and ELISA assay to further explore the role of DMF on the modulation of p38 MAPK pathway and VEGF levels production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, we have shown for the first time that DMF attenuates expression of VEGF mRNA and its release from RPE cells exposed to HG. Since the p38 MAPK pathway promotes and regulates the expression of pro-angiogenesis factors, including VEGF (Gomes and Rockwell, 2008;Sakai et al, 2017) we sought to determine whether VEGF decrease could rely on a DMF-induced p38 MAPK down-regulation. Therefore, we performed Western blot and ELISA assay to further explore the role of DMF on the modulation of p38 MAPK pathway and VEGF levels production.…”
Section: Discussionmentioning
confidence: 99%
“…However, DMF seems to have several biological effects as it has been shown to also inhibit the phosphorylated p38 MAPK (Nishioku et al, 2020;Kortam et al, 2021) thus blocking downstream targets that may be involved in the development and progression of inflammatory cascades leading to numerous diseases. In fact, it has been demonstrated that the activation of p38 MAPK signaling is required for VEGF expression in response to growth factors and cytokines stimulation (Gomes and Rockwell, 2008;Sakai et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Evidence has shown that VEGF, is produced by most parenchymal cells and acts in a paracrine manner on adjacent vascular cells to regulate neovascularization [22]. Recently, it has been reported that transforming growth factor-β (TGF-β) stimulated OBs could synthesis VEGF through the negative regulator heat shock protein 70 [49]. In vasculogenesis process, VEGF is indispensable for recruitment, retention, proliferation, differentiation, migration and capillary-like structure formation of EPCs [50, 51].…”
Section: Discussionmentioning
confidence: 99%
“…32 Dysregulation of HSPs is involved in a number of fibrotic conditions and different HSPs can either promote or inhibit TGFb signaling. [33][34][35][36][37] HSPs have also been investigated as potential therapeutic targets for fibrosis, either through inhibition (e.g., HSP90 inhibition reduces hepatic 38 and renal fibrosis 39 ) or induction (e.g., HSP70 induction reduces hepatic 40 and pulmonary fibrosis 41 ). These findings indicate competing roles for HSPs, and the relative importance of HSPs in fibrosis and wound healing is an area of ongoing research.…”
Section: Mechanismsmentioning
confidence: 99%